Alexander Polyhistor and Glaucus of Rhegium as Sources of Pseudo-Plutarch’s Treatise De musica. I–II - Almazova, Nina (Hyperboreus, 2022)
The role of Alexander Polyhistor as the source of Ps.-Plut. De mus. seems underestimated. The paper argues that in ch. 3–10 of his treatise the compiler regularly used Alexander to address the history of instrumental music (ignored by Heraclides of Pontus). Two mutually incompatible historical constructions, one identifying Amphion as the first citharode (ch. 3), and the other Orpheus (ch. 5), betray two different sources, neither of which took the other into account. These are most probably Heraclides and Alexander. The latter, in his turn, based his description of Phrygian impact in Greek music on the data of Glaucus of Rhegium, and it is from his book that all Glaucus’ quotations concerning the role of Olympus originate. A diffused assumption of Glaucus’ partiality to wind music may be misleading, if Polyhistor intentionally chose data dealing with Olympus’ influence for his “Collection of Information about Phrygia”.The first such quotation (ch. 5, p. 5, 7–11 Ziegler 1959) lacks the reference to Glaucus and must be attributed to him by its contents. The discrepancy between two phrases of Glaucus, one of which seemingly places Terpander immediately after the first inventors of  aulos music, the other inserting Orpheus between them, is eliminated by (a) referring αὐτὸν δεύτερον γενέσθαι (p. 5, 1) to Archilochus instead of Terpander and (b) interpreting οἱ τῶν αὐλῳδικῶν ποιηταί (p. 5, 10) as a scribe’s mistake prompted by ὁ τῶν αὐλῳδικῶν νόμων ποιητής immediately below (p. 5, 11–12).The next passage taken from Polyhistor is ch. 7, as the shared subject with ch. 5 clearly shows. Its particularly chaotic composition may be due to the fact that the compiler tried to compose a list of auletic nomes, which were not organized in a list in any of his sources, but was distracted now and then by the topics discussed in the books he used. The incongruity consisting in a reference to “above-mentioned” Olympus as the second one – where he was really the first – may be removed by changing εἶναι to ἔνιοι in p. 6, 24. The reference to Glaucus confirms the argument and thus forms an organic part of Alexander’s report on the Phrygian inventors of wind music. The mention of the instrumental Fig nome in ch. 8 lacks the “Phrygian trace” and was probably taken from Heraclides’ discussion on the need for archaic elegiac poets to master aulos-playing.At the same time, some of Glaucus’ chronological calculations (such as p. 4, 25 – 5, 2 and 5, 14–15) could be cited by Heraclides as well. If so, his treatise on ancient poets and musicians remained an important reference book for a certain period.